Ball-type supramolecular metallophthalocyanines with eight perfluorodecyl units: chemosensors for SO2 and electrocatalysts for oxygen reduction - ÖZKAYA, ALİ RIZA; ÖZER, METİN (ROYAL SOC CHEMISTRY, 2009)
Heptadecafluorodecyl-substituted cofacial or ball-type bis-metallophthalocyanines (BTMPcs) have been prepared. The redox properties of the complexes and their catalytic activities for oxygen reduction were studied. The occurrence of stepwise one-electron redox processes during the voltammetric measurements in solution suggested the formation of stable mixed-valence species of the complexes, as a result of the intramolecular interactions between two cofacial Pc units. The ball-type Co(II) complex displayed excellent catalytic activity for oxygen reduction which is probably due to the rigid cofacial structure involving two redox-active metal centers, which are capable of binding O-2. do and ac conduction properties of BTMPcs [M = Co(II) 3 and Cu(II) 4]thin films have been investigated in the frequency range of 40 to 10(5) Hz and temperature 290-440 K. The do results showed an activated conductivity dependence on temperature for all films. The analysis of the obtained data showed that the correlated barrier hopping (CBH) model is the dominant conduction mechanism for electron transport in the films. The gas sensing properties of the films for SO2 were also investigated over the same temperature range. Although a very high response to SO2 gas has been obtained for the film of 3 at room temperature, the film of 4 was not sensitive to the same gases.
Keywords: ELECTRICAL-PROPERTIES; CATALYTIC-REDUCTION; SENSING PROPERTIES; HYDROGEN-PEROXIDE; ELECTROREDUCTION; PHTHALOCYANINES; DIOXYGEN; WATER; ZINC(II); BIS